CHARACTERIZATION OF ALLOY TERNARY ZN -NI- CO ELECTRODEPOSITED BETWEEN ACID AND ITS CORROSION PROPERTY - Reátegui R., W. (2011)
The electrodeposition of the ternary alloy coating of Zn -Ni- Co using a solution containing zinc chloride ( ZnCl2 ) , cobalt chloride ( CoCl2.6H2O ) and nickel chloride ( NiCl2.6H2O ) . The crystalline phase , surface morphology and hardness of the alloys obtained were characterized by X-ray diffraction (XRD ) , atomic force microscopy (AFM) and microhardness , respectively . The chemical composition of the coating was measured by atomic absorption spectroscopy . The corrosion rate was measured with a potentiostat through the technique of linear polarization resistance . We found that the ternary alloys obtained have better corrosion resistance and higher hardness than the Zn coating . Under the conditions examined , the electrodeposition of ternary coating is the anomalous type . The crystalline phase of the alloy obtained on ordinary steel and copper is Zn11Ni2 phase .